Sexual Harassment/Abuse Policies in U.S. Youth Sport Programs - Kim, Sungwon (Journal of interpersonal violence, 2024)
Sport governing bodies, such as the International Olympic Committee, have recommended youth sport organizations develop policies, procedures, and/or ethical guidelines to prevent and respond to sexual harassment and abuse (SHA) experienced by young athletes. To our knowledge, no studies have investigated SHA policies or procedures in U.S. youth sport programs. The purpose of this exploratory study was to examine U.S. youth sport programs’ policies regarding SHA. The results are based on a cross-sectional survey completed by youth sport coaches (n = 200) from various organizations (e.g., public recreation organizations, private nonprofit organizations, and interscholastic sports). Findings suggest that most organizations have several SHA policies, such as education and training requirements, written policies and codes of conduct regarding coach-athlete sexual relationships, and formal complaint and disclosure procedures for investigating SHA. A bivariate analysis suggests that the presence of several SHA policies was associated with an increased number of self-reported SHA incidents. Moreover, youth sport programs located in urban areas had a greater extent of SHA policies compared to those located in suburban or rural areas. These results are discussed with respect to the potential relationships between the presence of policies and increased cases of SHA. Also, we discussed advocating for equitable resources among youth sport programs regardless of geographic and/or demographic factors. Future research should identify social and cultural barriers that inhibit the successful implementation of SHA policies. While developing and implementing SHA policies is a step in the right direction, it may not be used as the only means to address this complex, systematic, and structural issue.